Core features of Indian Muslim restaurant concept in West Malaysia / Mohd Hairi Jalis, Norhayati Husin and Mohaini Mohamed@Naba - Jalis, Mohd Hairi; Husin, Norhayati; Mohamed@Naba, Mohaini (2018)
Ethnic restaurant has been recognized as one of the fastest growing food outlets in Malaysia. One of the most successful ethnic restaurants found in Malaysia is Indian Muslim or popularly known as Mamak restaurant. Since early 2000, Indian Muslim restaurants are known for their 24 hours' of food business operation as well as the various food business operation models including cafeteria and table service styles. However, until today, scholars keep discussing and exploring the concept of Indian Muslim restaurant. It was also found that limited number of attention and detail are given by scholars on the core concept of ethnic restaurant especially the case of Indian Muslim restaurant in West Malaysia. Therefore, using existing literature and systematic observation, this study aims to explore and critically discuss the core features of Indian Muslim restaurant in West Malaysia within the concept of ethnic restaurant. From the content analysis, this study has discovered that menu item (i.e. the name of food and drinks), staff (i.e. ethnicity and physical appearance), and cooking style have significant contributions to uplift the identity of Indian Muslim restaurant. These features not only define Indian Muslim restaurant but also act as the core business attraction as well as strengthen a better understanding on the idea and concept of Indian Muslim restaurant especially in West Malaysia. In addition, the decoration of restaurant such as the choice of interior and exterior colors (i.e. mainly blue and green), wearing 'Songkok' (i.e. male Muslim hat) and hijab (i.e. waitress), and displaying wall frames that contain Arabic calligraphic on every corner of restaurant wall signify the notion of Islam and Halal among the Muslim customers. This an example of a Muslim Friendly Restaurant (MFR) concept within a combination framework of ethnic and religious. In summary, this study concludes that beyond serving a plate of food, Indian Muslim restaurant in West Malaysia also educates their customers and publics to learn and appreciate the uniqueness of the concept of ethnic itself.